ARTIFICIAL INTELLIGENCE IN PUBLIC ADMINISTRATION: AN ETHICAL DILEMMA - Vephkhvia Grigalashvili, (International Journal of Innovative Technologies in Social Science, 2025)
Integration of Artificial Intelligence (AI) into public administration has brought forth significant transformations, promising increased efficiency, data-driven decision-making, and enhanced public service delivery. However, these advancements come with profound ethical dilemmas that challenge the foundational principles of governance, including transparency, accountability, fairness, and public trust. This article explores the ethical implications of AI deployment within public sector institutions, drawing on recent scholarly literature from 2020 to 2025. Through a critical review of key sources this study identifies core ethical concerns arising from algorithmic opacity, bias in automated decision-making, erosion of human discretion, and the challenges of ensuring democratic oversight. The research demonstrates that while AI has the potential to augment administrative capacity, its application must be cautiously governed to avoid reinforcing systemic inequalities or diminishing civic participation. Moreover, the global disparity in AI governance readiness underscores the importance of context-sensitive frameworks and culturally adaptive norms. This article contributes to the ongoing debate by synthesizing theoretical insights with practical implications, thereby informing both scholars and policymakers on how to ethically integrate AI in the public sector. The findings suggest that a balance must be struck between innovation and ethical responsibility, demanding new regulatory mechanisms, stakeholder engagement models, and cross-disciplinary dialogue. In doing so, the paper advocates for a cautious yet forward-looking approach to AI in public administration, aligning technological advancement with democratic values and public interest.